From Awareness to Practice: EFL Teachers’ Engagement with SDG 4 (Quality Education) in University Classroom Instruction - Omran, Sara; Alouzi, Khuloud; Alshineeti, Aml; Alatrish, Entisar; Alfallah, Bushra; Abouzied, Abdulghani; Elbi, Mohamed (LPPM Universitas Pancasakti Tegal, 2025)
This study investigates university English (EFL) lecturers’ awareness, attitudes, and classroom practices related to Sustainable Development Goal 4 (Quality Education). It focuses on the gap between understanding SDG4 and applying it in teaching practice. A quantitative research design was adapted. Data were collected through a questionnaire distributed to 100 university EFL lecturers. The questionnaire examined the lecturers' awareness of SDG 4, their attitudes towards its integration in their teaching practices, institutional support, perceived challenges, and lecturers' self-efficacy. The findings show moderate to high awareness of SDG 4 and strongly positive attitudes toward its integration in EFL instruction. However, the level of classroom implementation was only moderate, indicating a clear gap between awareness and practice. While inclusive and learner-centered strategies were commonly used, the direct integration of sustainability themes and SDG-related targets was inconsistent. Limited institutional support, insufficient professional development opportunities, and curriculum constraints emerged as the most significant challenges. Despite these challenges, lecturers reported a strong willingness to engage in training and showed a clear intention to expand SDG in future practice. The study concludes that EFL lecturers are motivated and prepared ethically to support SDG. However, effective and sustained implementation needs higher institutional support, targeted professional development, and supportive policy frameworks. The findings highlight the important promoting role of language education in promoting quality, inclusive, and globally oriented higher education.